The artist as social worker vs. the artist as social wanker*. (2nd January 2018) - Schrag, Anthony
ABSTRACT: This paper briefly explores the problematic notion of the "artist as a social worker" and aims to develop an (ethical) counterpoint to this position via Mouffe's concept of agonism. It begins by tracing some conceptual frameworks that have posited art as an ameliorative force within the public realm, discusses the complications of "intention" embedded in language, as well as draws attention to the difference between these terms that are often interchangeably. It ends with an exploration of three agonistic artworks, the last being the author's own. It hopes to present a productive counterpoint to the notion of the "artist as social worker, " as well as provide insight to these discussions from a practitioners point of view.